The School of Sharīʿa Judges: Sharīʿa Courts’ Reform and Legal Modernization in Egypt (1907-1927) - Nouh, Yamen (AUC Knowledge Fountain, 2023)
This thesis studied the history of the school of sharīʿa judges (1907-1927) as an essential episode of the reform of Sharīʿa courts in Egypt in the early 20th century. The thesis studied the school in connection with the broader context of legal modernization of the Egyptian legal system. The study explored the institutional, pedagogical, and legal aspects of the reform that the school advocated. The study analyzed the impact of the school’s pedagogy on the practice of the Islamic judiciary and the theoretical conception of Sharīʿa. The study used a significant yet understudied historical source: the judicial press. A comparative analysis was made between two important judicial periodicals. The first one is the Majallat al-Aḥkām al-sharʿiyya (Journal of sharīʿa verdicts), which was in publication between 1902 and 1909, and the second one is the Majallat al-Qaḍāʾ al-sharʿī (the journal of sharīʿa judiciary) that was in press between 1922 and 1931, edited and published by the school of sharīʿa judges’ students and graduates. Both journals published a plentiful number of complete court records along with legal comments on them. Both journals also provide a perfect source for understanding the debates and conflicts regarding the sharīʿa courts’ system through the articles authored by judges and clerks of the courts. Both journals were issued on two different phases of reform, which provided a perfect comparative perspective. The thesis argued that a specific vision of legal pedagogy was set for the school by the British colonial authorities to induce a reform of Islamic judicial practice. That reform was meant to harmonize the practice of the sharīʿa courts with Modern tribunals (i.e., National and Mixed courts) in preparation for its dilution and abolition. That reform led to a remarkable change in the judicial practice of the school’s graduates. It also led to a fundamental transformation of the notion of sharīʿa in their legal writings, from a dynamic legislative methodology, as it used to be approached in the pre-modern Islamic judiciary practice, to a static legal theory, following the Frech legal theoretical model.